Asuhan Keperawatan Keluarga Nyeri Akut Pada Klien Dengan Gastritis : Studi Kasus - Iswatun Iswatun; Endah Sri Wijayanti; Aini Nurul Fatimatuz Z (Surya : Jurnal Media Komunikasi Ilmu Kesehatan, 2021)
Background: Gastritis is a problem experienced by many people and can occur at any age. Gastritis is a disease that occurs due to inflammation of the stomach caused by an increase in stomach acid. The most common symptom in gastritis clients is acute pain.Objectives: The purpose of this case study is to carry out Family Nursing Care with Acute Pain for Gastritis Clients in Ngadirejo Village, Widang District, Tuban Regency.Design: This research method uses a case study method with a family nursing process approach, with research subjects 5 gastritis clients with acute pain. Data collection was obtained through interviews, observations, physical examinations, and documentation studies. The data obtained were analyzed by comparing theory with cases, made in a descriptive narrative.Results: The results of the case study showed an assessment of the suitability and discrepancy, 2 clients said the pain was reduced when they were made to sleep on their stomach, 3 clients said the pain was reduced when they were sleeping on their side. Nursing diagnosis leads to acute pain. Interventions were made according to the literature review, focusing on pain management. Implementation is in accordance with predetermined interventions. On evaluation, the diagnosis of acute pain, can be resolved in 3 visits.Conclusions: Pain management by providing distraction and relaxation techniques is very effective in reducing pain in gastric clients. It is hoped that the family is able to take promotive and preventive actions and can play an active role in meeting the needs of the client, so that the family can carry out nursing care independently. Key Word : Family Nursing Care, Acute Pain, Gastritis